PERSPEKTIF TEORI WACANA VAN DIJK DALAM PIDATO PERDANA PRABOWO-GIBRAN USAI DITETAPKAN KPU JADI PEMENANG PILPPRES - Br Tarigan, Cindy Claren; Sapta Rindu Simanjuntak, Dairi; Simbolon, Ronaida; Harefa, Boisman; Pandiangan, Friska; Aritonan, Riwando; Elfrida Simatupang, Dina; Br Purba, Rika (Jurnal Bahastra, 2024)
This research discusses the video broadcast of Prabowo-Gibran's first speech which was broadcast on the KompasTV YouTube media with the title "Prabowo-Gibran's First Speech after the KPU Legally Determines the Winner of the Presidential Election: Merdeka". The aim of this research is to analyze discourse elements using the Teum A model. The research method used in this research is descriptive qualitative. The data analysis technique used by the researcher is using content analysis and note taking to analyze the form or structure of sentences used by Prabowo-Gibran and the researcher found an emphasis made by using images, word order in the title, bolding of letters, use of capital letters, colons, and so on on the cover (clickbait) of videos broadcast on the KompasTV YouTube channel. The results of the analysis carried out by researchers are of course different from other videos broadcast on YouTube, this is due to ideological differences, the message to be conveyed in the discourse, the packaging in a video and so on